Redesign of Road Geometric Civil 3D® Case Study: Jl. Kadipaten-Kasokandel (STA 0+000-STA 4+800) - Yoga Setyawan (LEADER: Civil Engineering and Architecture Journal, 2024)
Geometric road planning is a component of road development planning that aims to determine the actual dimensions of the road and its function to meet traffic needs. In the geometric planning of the Kadipaten-Kasokandel road at STA 0+000-STA 4+800, geometric patterns and shapes must be planned so that the related streets can produce optimal service to traffic according to their function. Road geometric planning on the Kadipaten-Kasokandel the segment of the road from Sta 0+000 to Sta 4+800 using AutoCAD®Civil 3D using the design speed plan (VD) criteria of 80 km/hour, the terrain classification on this road section is flat terrain. In the horizontal alignment, there are four bends with three curves using the Spiral-Circle-Spiral type, while the first use the Full Circle bend type. In the vertical alignment, there are seven segments of the inclined plane.